An optimized separation process of microalgal lipidic products by molecular distillation: Techno-economic analysis. (2nd November 2019) - Mazzelli, A.; Luzzi, D.M.; Buonanno, G.; Cicci, A.; Piemonte, V.; Iaquaniello, G.
Highlights: Optimal working conditions for molecular distiller are T = 128 °C and P = 0.33 Pa. Adsorption columns to separate water (Length = 1 m, Radius = 0.2 m) are designed. The esterification reactor volume needed to reach a conversion of 97% is 3 m 3 . Estimated OPEX and CAPEX give an overview of the process' feasibility. Abstract: Microalgae are a sustainable rich source of high-added value metabolites, as omega-3 and carotenoids, for their ability to grow and accumulate these compounds also in wastewaters or in seawaters. Molecular distillation is a valid techinque respect to conventional distillation for fractionation of these thermosensitive products without affecting their nutritional and biological values. In this work a fractionation process using molecular distillation for separating fatty acids (in part omega-3) as esters and carotenoids from a microalgal lipidic extract, was designed and optimized. A Response Surface Method (RSM) analysis was carried out in order to find the optimal operative conditions of the molecular distiller in terms of temperature, pressure and purification ability. Furthermore, to complete the process scheme, also the design of the other equipments, including in particular the esterification reactor and the dewatering column, was done. In order to complete the feasibility study of the process, an estimation of the Operating Expense (OPEX) and Capital Expenditure (CAPEX), using the results of the simulations in terms of energy and utilities' consumption, was done. All of these informations, both technical and economical, will be the basis for future industrial implementations of the designed process.